Hubungan Tingkat Kemandirian terhadap Kejadian Arthritis Rheumatoid pada Lansia di wilayah kerja Puskesmas Tinangkung Utara kabupaten Banggai Kepulauan - Trisinta Trisinta; Suaib Suaib; Benny Harry L. Situmorang (PPNI UNIMMAN, 2025)
Independence refers to the freedom to act and the ability to control one’s own or a group’s activities to protect oneself or others from various diseases or conditions. Among the elderly, the ability to perform Activities of Daily Living (ADL) often declines, which in turn reduces their independence in carrying out daily activities such as dressing, toileting, climbing stairs, or moving around. One of the common health problems affecting older adults is rheumatoid arthritis—an autoimmune disorder that causes inflammation and swelling in the joints, often affecting one or both sides of the body, making it difficult for the elderly to perform routine tasks. This study aims to determine the relationship between the level of independence and the incidence of rheumatoid arthritis among the elderly in the working area of Tinangkung Utara Public Health Center, Banggai Kepulauan Regency. This research employed a quantitative approach using the Chi-Square test. The study involved 50 respondents selected through a non-probability purposive sampling technique. The results of the Chi-Square analysis showed a p-value of 0.002 with a significance level of < 0.05, indicating that the research hypothesis was accepted. This finding means there is a significant relationship between the level of independence and the occurrence of rheumatoid arthritis among the elderly in the study area. In conclusion, the level of independence influences the occurrence of rheumatoid arthritis in older adults. Therefore, it is highly recommended that the elderly maintain active and independent movements as a way to keep their joints healthy and functional..